Nonautonomous mixed mKdV-sinh-Gordon hierarchy - Gomes, J. F. [UNESP]; de Melo, G. R. [UNESP]; Ymai, L. H. [UNESP]; Zimerman, Abraham Hirsz [UNESP] (Iop Publishing Ltd, 2010)
The construction of a nonautonomous mixed mKdV/sine-Gordon model is proposed by employing an infinite-dimensional affine Lie algebraic structure within the zero-curvature representation. A systematic construction of soliton solutions is provided by an adaptation of the dressing method which takes into account arbitrary time-dependent functions. A particular choice of those arbitrary functions provides an interesting solution describing the transition of a pure mKdV system into a pure sine-Gordon soliton.